A Comparison of Optimal Training Load for Maximal Power Output in Upper and Lower Body Exercises According to Different Sports - Bayrakdaroğlu, Serdar; Can, Ibrahim; Ulutaşdemir, Nilgün (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this study was to compare optimal training load which maximizes power output in both lower and upper body exercises for athletes competing in different sports. Methods: To achieve this, a total of sixty athletes from different sports (football, handball, arm-wrestling, volleyball, wrestling, and martial arts) volunteered for the study. To determine the lower and upper body strength characteristics, bench press (BP) and full squat (SQFull) exercises were performed in the research. To determine the mean propulsive power (MPP), the participants executed bench throw (BT) and loaded-squat jump (SJLoad) exercises using an external load corresponding to 30% and 40% of their body weight respectively for the upper body the lower body (10% increments until reaching the maximal power value) via an isoinertial velocity transducer ( T-Force dynamic measurement system). One-way analysis of variance, test of significance between two means, and correlation analysis were used in the study. Results: The results showed there was a statistically significant difference according to different sports in terms of maximal power value and optimal training load for the MPP parameter in both SJLoad and BT exercises. Conclusion: Consequently, it can be claimed that the optimal load value for maximal power output in exercises include shows dissimilarity according to different sports, and individuals need to perform their training by using the load value capable of maximizing their power output.